The Legal Basis of Public Participation in the International Environmental Governance as a Requirement for Sustainable Development - Pavlova, Olga V. (European Journal of Sustainable Development, 2017)
The paper focuses on the global environmental governance and features of public participation as an integral element of sustainable development. Recently, sustainable development and environmental governance have become interrelated elements of social development. The requirements to strengthen the role of civil society, especially representatives of the public, under the new or reformed system of international environmental governance are important issue of the article. The civil society should play a major role in five key areas: collection and dissemination; policy development consultation; implementation of environmental policy; monitoring and evaluation; promotion of environmental justice. The author defines the features of powers’ separation between the actors in international environmental governance, enlightens the question of the public environmental management and its role in environmental decision-making. Thus, determination of the usefulness of the international environmental governance model for the national systems of law is up to date. The research of the peculiarities of the realization of public participation in the international environmental governance is consider to be of the highest relevance, and the development of public environmental management as a distinct element of environmental governance is the issue for the further investigations. Keywords: public, public environmental governance, international environmental governance, sustainable development, public participation.